Resistive Matching Techniques in Electrical Balanced Duplexer Systems - Spielberger, Alexander; Pfannenmüller, Christof; Weigel, Robert; Fischer, Georg (Asia-Pacific Microwave Conference 2024, 2024)
Electrical Tunable Duplexers allow multi-use of RF front ends. A broadband impedance tuner is required for high isolation. This paper deals with how the use of a Digital Tunable Resistor (DTR) can improve the tuning range of such a tuner. In the following a possible DTR realization is shown, which converts a linear control voltage into a linear relation of the reflection coefficient. This can be used to map a reflection coefficient of -0.9 to 1 up to a frequency of 6 GHz. <br
Keywords: electrical balanced duplexer; mobile communication; resistive matching; digital tunable resistor